The Payment System and Monetary Policy - Johnson, Omotunde (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1998)
Achieving the primary objective of price stability without unduly compromising the operational efficiency of the payment system constitutes a major problem for central banks. Routine monetary policy presumes a given institutional and technological framework, including aspects of the payment system. Such a monetary policy concerns itself with intraday and interday credit for payments settlements and with float. Liquidity shocks and panics sometimes pose an additional challenge. In recent years, major and rapid institutional and technological changes in the payment system (mainly to lower risks and augment operational efficiency) have affected the monetary policy decision-making process, particularly in the short run.